Field Tests Of Soft Clay Stabilized By Stone Columns In Coastal Areas In China (325b7cc0-aff5-4a88-9f69-cd3dc2f57f1d) - Han Jie (Deep Foundations Institute, 1991)
The results of full scale plate load tests on stone columns on soft clay in coastal areas are presented in this paper. Four load tests were made, two of which were performed on the ground treated with stone columns, one on an isolated stone column and the last one on the untreated ground. For a given stress range, the settlement of the rigid plate, the stress concentration factor, and the excess pore water pressure were measured. It is found that the distribution of vertical stress beneath the rigid plate supported by the composite ground of stone columns is very different in shape from the one by the untreated ground, that the stress concentration factor has a relation with the stress level and time, that the stone columns increase the bearing capacity up to by 2 times, and that the ground stabilized by stone columns is of great advantage to keep the foundation stable.